Transient low T3 syndrome in patients with COVID-19: a new window for prediction of disease severity - Zhong, Mingyao; Gao, Yue; Hu, Hongling; Zhu, Xuan; Gan, Lulu; Li, Ling; Xiang, Cheng; Yan, Yimin; Dai, Zhe (Frontiers in Endocrinology, 2023)
Objective: To investigate the relationship of low T3 syndrome with disease severity in patients with COVID-19. Methods: The clinical data of 145 patients with COVID-19 were retrospectively collected, and patients were divided into a low T3 group and a normal T3 group. Kaplan-Meier analysis was used to analyze the impact of low T3 syndrome on mortality, and receiver operating characteristic (ROC) analysis was used to evaluate the use of low T3 syndrome in predicting critical disease. Results: Fifty patients (34.48%) were in the low T3 group and 95 (65.52%) were in the normal T3 group. Six patients in the low T3 group and one patient in the normal T3 group died. The low T3 group was older, and had lower levels of hemoglobin, lymphocytes, prealbumin, and albumin, but higher levels of white blood cells, D-dimer, glutamic-oxalacetic transaminase, lactate dehydrogenase, fasting blood glucose, CRP, and ESR (all p<0.05). The low T3 group had greater prevalences of respiratory failure, critical disease, and mortality (all p <0.05). Kaplan-Meier analysis showed the low T3 group had increased mortality, a lower level of lymphocytes, and an elevated level of D-dimer (all p<0.001). ROC analysis showed that free T3 (FT3), lymphocyte count, and D-dimer, and all three parameters together provided reliable predictions of critical disease. All 42 patients whose T3 levels were measured after recovery had normal levels after discharge. Conclusion: Patients with COVID-19 may have transient low T3 syndrome at admission, and this may be useful for predicting critical illness.